What is masculinity? historical dynamics from antiquity to the contemporary world - Arnold, John 1969-; Brady, Sean 1964- (Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2013)
What is masculinity? Looked at across time - from antiquity to the modern day the contours of 'manliness' take on an intriguing complexity. As the various contributors to this volume demonstrate, the ideas and practices of male identity have varied considerably over time and place: masculinity proves to be a slippery concept, one not available to all men, and one sometimes even applied to certain women. This ground-breaking book presents a variety of new perspectives on the nature of masculinity, its social and political functions, and the methods by which historians and others might seek to analyse it. Each author provides both a case study of what masculinity means (or fails to mean) in a specific historical moment, and contributes to a wider collective analysis of the changing historical dynamics to male identity. Overall, the book provides a key methodological landmark in the study of gender history.
Introduction / John H. Arnold and Sean Brady -- The history of masculinity : an outdated concept? / John Tosh -- Can the hegemon speak? : reading masculinity through anthropology / Diederik F. Janssen -- The Whig interpretation of masculinity? : honour and sexuality in late medieval manhood / Christopher Fletcher -- Masculinity without conflict : noblemen in eighth and ninth-century Francia / Rachel Stone -- Masculinities in early Hellenistic Athens / Henrik Berg -- Masculinity as a world historical category of analysis / Simon Yarrow -- Hegemonic masculinities? : assessing change and process of change in elite masculinity, 1700-1900 / Henry French and Mark Rothery -- Masculinity and fatherhood in England c. 1760-1830 / Joanne Bailey -- Athenian pederasty and the construction of masculinity / Thomas K. Hubbard -- An orchard, a love letter, and three bastards : the formation of adult male identity in a fifteenth-century family / Rachel E. Moss -- 'To make a man without reason' : examining manhood and manliness in early modern England / Jennifer Jordan -- 'Boys, semi-men and bearded scholars' : maturity and manliness in early nineteenth-century Oxford / Heather Ellis -- St. Francis of Assisi and the making of settlement masculinity, 1883-1914 / Lucinda Matthews-Jones -- Homes fit for homos : Joe Orton, masculinity, and the domesticated queer / Matt Cook -- Three faces of fatherhood as a masculine category : tyrants, teachers, and workaholics as 'responsible family men' during Canada's baby boom / Robert Rutherdale -- Cow boys, cattle men, and competing masculinities on the Texas frontier / Jacqueline M. Moore -- Valorising samurai masculinity through biblical language : Christianity, Oscar Wilde, and Natsume Soseki's novel Kokoro / Kasumi Miyazaki -- 'Proper government and discipline' : family religion and masculine authority in nineteenth-century Canada / Nancy Christie -- Punters and their prostitutes : British soldiers, masculinity, and maisons tolâerâees in the First World War / Clare Makepeace -- Masculinities, histories, and memories / Victor Jeleniewski Seidler.
Includes bibliographical references and index.
Keywords: Masculinity -- History; Gay men -- Identity; Gay men -- Conduct of life; Gay men -- Social conditions; Gender identity